2020
DOI: 10.3399/bjgpopen20x101004
|View full text |Cite
|
Sign up to set email alerts
|

Defining when specialised mental health care is needed: a focus group study

Abstract: BackgroundShared understanding between GPs and hospital specialists concerning when patients need specialised mental health care is important to ensure patients receive appropriate care. The large amount of rejected referrals often indicates a lack of such shared understanding.AimTo explore how patient representatives, GPs, and mental health specialists understand ‘need for specialised mental health care’, meaning that primary care is no longer sufficient.Design & settingThis qualitative study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Determining what is an appropriate level of engagement is difficult and this is highlighted in the above examples of the dynamic discussion that occurs within consultations. Physical symptoms taking precedence, 1 , 25 time limitations, 1 and confidence 26 may influence the level of engagement in a consultation. For example, headaches can be a symptom of underlying pathology and impact quality of life, therefore warranting further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Determining what is an appropriate level of engagement is difficult and this is highlighted in the above examples of the dynamic discussion that occurs within consultations. Physical symptoms taking precedence, 1 , 25 time limitations, 1 and confidence 26 may influence the level of engagement in a consultation. For example, headaches can be a symptom of underlying pathology and impact quality of life, therefore warranting further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, specialized mental health care refers to secondary care provided by health care specialists in psychiatric hospitals and district psychiatric centers. Treatment in these settings is provided when primary health care is no longer deemed sufficient for the patient's needs (Nymoen et al, 2020). Norwegian legislation and guidelines prioritize patient treatment in specialized mental health care in relation to the intensity and frequency of symptoms and functional level and the expected impact of treatment on the patient's quality of life (Norwegian regulations of priority between patients in health care, 2000; The Norwegian Directorate of Health 2015).…”
Section: Settingmentioning
confidence: 99%
“…Norwegian legislation and guidelines prioritize patient treatment in specialized mental health care in relation to the intensity and frequency of symptoms and functional level and the expected impact of treatment on the patient's quality of life (Norwegian regulations of priority between patients in health care, 2000; The Norwegian Directorate of Health 2015). Usually, specialized mental health care is considered the appropriate level of treatment if patients are assessed to have limited ability to function in daily life, have symptoms of psychosis and/or are at risk of self-harm or risk of harming others (Nymoen et al, 2020).…”
Section: Settingmentioning
confidence: 99%
“…One study points to possible weaknesses in the prevailing Norwegian model, as it found low agreement between the teams when comparing triage decisions based on written referrals [ 17 ]. Another weakness observed in today’s triage process is that there is often no common understanding between the referrer and the hospital specialist regarding the necessity of more specialised treatment [ 18 ].…”
Section: Introductionmentioning
confidence: 99%